HTML5-based Visualizations to Support Software Fault Isolation - Carlos Miguel de Sousa Gouveia (2013)
Testing and debugging is the most expensive, error-prone phase in the software development life cycle. Automated software fault localization can drastically improve the efficiency of this phase, thus improving the overall quality of the software. Amongst the most well-known techniques, due to its efficiency and effectiveness, is spectrum-based fault localization. In this project, we propose three HTML5-based dynamic graphical forms to display the diagnostic reports yielded by spectrum-based fault localization. The visualizations proposed, namely Sunburst, Vertical Partition, and Bubble Hierarchy, have been implemented within the GZOLTAR toolset, replacing previous and less-intuitive OpenGL-based visualizations. The GZOLTAR toolset is a plug-and-play plugin for the Eclipse IDE to ease world-wide adoption. Finally, we performed an user study with GZOLTAR and confirmed that the visualizations help to drastically reduce the time needed in debugging (e.g., all participants using the visualizations were able to pinpoint the fault, whereas of those using traditional methods only 35% found the fault). The group that used the visualizations took on average 9 minutes and 17 seconds less than the group that did not use them.